Headscarf politics in Turkey : a postcolonial reading - Islam, Merve Kavakçı (Palgrave Macmillan, 2010)
Covering of Muslim women is often perceived as a sign of oppression in the Western eye. Nonetheless, there are a soaring number of women who choose to wear the Islamic headgear as a sign of their liberation and commitment to God. Although these women have long been of interest for the peoples of the Occident with endless material produced about them in the past, it was invariably through the monotonal voice of the Orientalist from a position of outside authority. Here the reader will hear, for a change, the insiders' voices from within the Orient, the voices of the contemporary Turkish women who cover, willingly and yes, decisively. Their day to day struggles in search for their niche in the secular Turkish society is intended to open a new window and provide an alternative perspective for the Western reader.